The Museum That Would Not Die: The Strange Persistence of the Maine State Museum - Fishman, Bernard (Maine Policy Review, 2015)
Maine is the only New England state with a substantial state museum supported in large part by state appropriations. The present museum can be said to have been founded in 1836, but it was closed or eliminated six times over the next 135 years before being resurrected for the seventh time in 1971. In this article describing the history of the Maine State Museum, museum director Bernard P. Fishman argues that its perseverance arises from basic communal and indeed human needs and also from Maine’s particular circumstances.
Keywords: Maine State Museum; museums